A percepção dos publicitários brasileiros sobre a ferramenta de comunicação de marketing Branded Content - Kalil, Jefferson Vasques (2007)
The conducted survey intended to verify the perception of Brazilian advertising agents in relation to the following phenomena: the potential of Branded Content and product placement, and the impact of technological advances on the effectiveness of publicity in television. To do so, a qualitative research was developed by using the analysis content technique. The universe to be studied, from which a sample of 10 advertising agents was extracted, was formed by advertisers from the media, planning or creation, who work in any of the 35 biggest advertising agencies in Brazil. The agencies headquarters are in the city of Sao Paulo and they are not agencies of exclusively one client. The interviews were semi-structured with relatively open guide questions, following a pre-determined plan. The data analysis technique used was the enunciation analysis, which is a specific type in the field of content analysis. The results indicate that in Brazil, there are three factors that diminish the impact of technological advances on effectiveness of publicity in television: the Brazilian socio-economic structure, the sheer predominance of Globo Network and the quality of Brazilian television together with the fact that Brazilian people like commercials. Concerning audience fragmentation, most advertising agents emphasized a decrease in the effectiveness of publicity in television especially among young audiences, due to the fact that they are more open to adopting new technologies. In relation to the perception of product placement, the majority of advertising agents believe in its potential with the following restrictions: a greater integration between product and content and attention to the excessive number of actions in the same program. In relation to Branded Content, most advertising agents believe it to be only another tool at their disposal. On the other hand, three of them believe the Branded Content to be a future tendency, mainly because of the importance of appropriation of content by announcers